New profit models for property management in the post-pandemic era: A study on consumer attitudes towards community value-added services. - Meng Lin; Weidong Li; Yukun Cao; Yujuan Gao (PLoS ONE, 2024)
The COVID-19 pandemic, which emerged in 2020, has had a tremendous impact on various industries and the daily lives of the general populace, thereby contributing to increasing uncertainty in business competition. Property management enterprises, despite witnessing a mostly stagnant expansion and enhancement of their existing operations, have, owing to the unique nature of their services, continued to experience a relatively positive competitive environment. Notably, the recent emphasis in property management companies has been on the development of value-added services at the community level, which represents a critical avenue for securing a competitive edge by addressing consumer demands. This study, grounded in the ABC theory and the theory of planned behavior, seeks to analyze consumer attitudes towards the provision of value-added services by property management firms, including facets such as community healthcare services, community lifestyle amenities, community educational offerings, and personalized services. Moreover, the study delves into the mediating role played by satisfaction with fundamental property management services. The empirical findings emphasize the significant enhancement in consumer receptivity to property management firms' value-added services, particularly in the domains of community healthcare, lifestyle amenities, education, and personalized services. In addition, it highlights the indirect effect of property owners' contentment with essential property management services on their perspectives concerning the delivery of value-added services by property management firms. The implications of these research conclusions bear significant relevance for organizations engaged in offering such services.